SI TAMEN PLURES PER SE NAVEM EXERCEANT. KILKA UWAG O ODPOWIEDZIALNOŚCI ARMATORÓW - Służewska, Zuzanna (Zeszyty Prawnicze, 2017)
Si tamen plures per se navem exerceant. Several Remarks on the Liability of Shipowners Summary The problem discussed in this paper regards the liability of several shipowners (exercitores) managing the same ship. In the title de exercitoria actione o f the Digest there are three texts that refer to this matter: D. 14,1,1,25; D. 14,1,4 pr. and D. 14,1,4,1. The first and the last one refer to a situation in which the shipowners appointed a captain (magister navis) as their agent and thus were held liable in solidum for contracts made by him with third parties. In these cases their joint and several liability had ground in the joint appointm ent of an agent (praepositio). The second text D. 14,1,4 pr. is not very clear and refers to shipowners that were managing the same ship per se, and in this case they could be sued pro portionibus exercitionis. Such a model of liability was justified by the reservation that they cannot be deemed as being each other’s captain (neque enim invicem sui magistri videbuntur). This text was widely discussed among romanists and gave ground to various interpretations. The main questions concerned were the following: whether shipowners dealt with the third parties personally or appointed an agent (magister navis), whether a contract was stipulated by all shipowners jointly or only one o f them, whether they were partners in a partnership or conducted their business independently. According to the most common interpretation the text refers to a situation in which the shipowners conducted their activity personally in the partnership. Having accepted the above view, to justify their liability pro portionibus exercitionis one must admit that they all acted as a party in a contract or, supposing a contract was stipulated by one of them, a partnership between shipowners was a particular kind of partnership in which a contract concluded by only one of the partners resulted in the liability of the others. N one of these interpretations seems to be convincing. First of all, one must take into consideration that the word exercitor was a technical term used to define someone conducting an economic activity through his agent (magister navis) so it was normally used in the context of the whole structure of exercitio navis that was based on the scheme exercitor — magister navis. Thus it seems more likely that exercere per se means not conducting an activity personally but rather „on one’s own account”, „independently”. Besides, the reservation neque enim invicem sui magistri videbuntur suggesting that plures exercitores conducted their activity personally is dubious since it refers to a concept of mutual praepositio, which was used by glossators and commentators to justify joint and several liability of partners and it may be possible that this reservation constituted a part of the gloss or was added to the original context later by some interpreter that did not understand Ulpian’s intention. A similar conclusion arises from the comparison of the text of D. 14,1,4 pr. with texts concerning the liability of several persons on the basis of actio institoria. From the text of D. 14,3,14 it appears that if no legal relationship that guaranteed the possibility of a recourse existed among several persons liable for the act of the agent, none o f them could be sued for the full am ount (in solidum) but they were held liable pro parte. In the case of actio institoria the fact of a joint appointm ent was probably treated as a manifestation of animus societatis that made it possible to treat the persons that had nom inated jointly the institor as partners and thus held them liable in solidum for contracts made by this agent. Hence the fact that in the text o f D. 14,1,4 pr. the shipowners did not appoint jointly their agent and were held liable pro portionibus exercitionis suggests that they were not partners but each of them managed a ship on his own account. If we adm it that plures exercitores that per se navem exerceant were the shipowners that did not conduct their business together we could indicate two situations in which they could be sued pro portionibus exercitionis. The first would be the case in which each o f the shipowners appointed his own agent on the ship and the contract with the third party was stipulated by all agents acting together. The second would be the case in which the shipowners appointed the same person as their agent but the praepositio was given by each o f them separately. in both cases each o f the shipowners could be sued with actio exercitoria only for his proper part since they could not be deemed to be partners and they could not sue each other with any action for a recourse.